2019
DOI: 10.7150/thno.31032
|View full text |Cite
|
Sign up to set email alerts
|

Prospective non-invasive evaluation of CXCR4 expression for the diagnosis of MALT lymphoma using [68Ga]Ga-Pentixafor-PET/MRI

Abstract: MALT lymphomas express the chemokine receptor CXCR4 on a regular basis, and [68Ga]Ga-Pentixafor-PET has been shown to quantify CXCR4 expression non-invasively. We, therefore, aimed to evaluate [68Ga]Ga-Pentixafor-PET/MRI for the non-invasive assessment of MALT lymphomas. Methods: We included 36 MALT lymphoma patients, who had not undergone previous systemic or radiation therapy, in our prospective, IRB-approved, proof-of-concept study. Involved anatomic regions were the orbit (n=14), stomach (n=10),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 17 publications
1
37
1
Order By: Relevance
“…inflammatory conditions (Bouter et al, 2018). Examples of clinical applications in oncology are the detection of neuroendocrine tumors, multiple myeloma (Pan et al, 2018), glioma, leukemia (Mayerhoefer et al, 2018) or lymphoma (Luo et al, 2019;Haug et al, 2019). Since the precursor PentixaFor was made available until summer 2018 only for use by the synthesis module from Scintomics®, only hospitals that operated a Scintomics® module were able to prepare [ 68 Ga]Ga-PentixaFor.…”
Section: Introductionmentioning
confidence: 99%
“…inflammatory conditions (Bouter et al, 2018). Examples of clinical applications in oncology are the detection of neuroendocrine tumors, multiple myeloma (Pan et al, 2018), glioma, leukemia (Mayerhoefer et al, 2018) or lymphoma (Luo et al, 2019;Haug et al, 2019). Since the precursor PentixaFor was made available until summer 2018 only for use by the synthesis module from Scintomics®, only hospitals that operated a Scintomics® module were able to prepare [ 68 Ga]Ga-PentixaFor.…”
Section: Introductionmentioning
confidence: 99%
“…Stollberg S. and the colleagues found that CXCR4 expression was present at a high intensity in 92% of the cases [ 22 ]. In a recent study of MALT lymphoma, 33/36 patients were positive on [ 68 Ga]pentixafor PET/MRI showing a high uptake of [ 68 Ga]pentixafor [ 10 ]. Another head-to-head comparison study of [ 68 Ga]pentixafor and [ 18 F]FDG revealed that 95.2% of marginal zone lymphoma patients had positive lesions on [ 68 Ga]pentixafor PET/CT, as compared to only 42.9% of the patients who were positive on [ 18 F]FDG PET/CT [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical application of [ 68 Ga]pentixafor PET has been carried out in patients with non-Hodgkin lymphoma and multiple myeloma, which confirmed the CXCR4 expression in these lymphoproliferative diseases as a proof-of-concept [ 4 ]. Since then, most studies of [ 68 Ga]pentixafor were focused on evaluation of hematologic malignancies, for example, multiple myeloma [ 1 , 5 7 ], Waldenström macroglobulinemia/lymphoplasmacytic lymphoma [ 8 , 9 ], mucosa associated lymphoid tissue (MALT) lymphoma [ 10 ], chronic lymphocytic leukemia [ 11 ], and acute myeloid leukemia [ 12 , 13 ]. Some studies showed remarkable superiority of [ 68 Ga]pentixafor PET in detecting tumors and staging of the disease when compared with [ 18 F]FDG PET [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated the potential of CXCR4 as a theranostic target in MM patients in a pilot study confirming the feasibility of CXCR4-directed radionuclide therapy using 177 Lu or 90 Y-CXCR4 ligand (pentixather) as a novel treatment approach for MM [ 39 ]. Interestingly, compared to 18 FDG, 68 Ga-pentixafor also seems to be a promising imaging tool for assessment of other related blood cancers including MALT lymphoma [ 40 ], Waldenström macroglobulinemia, lymphoplasmacytic lymphoma [ 41 ] and primary central nervous system lymphoma [ 42 ]. Furthemore, the use of 11C-methionine (MET) in MM also seems to have a promising future.…”
Section: Perspectivementioning
confidence: 99%